PENGEMBANGAN E-MODUL BERBASIS APLIKASI CANVA PADA MATERI MENULIS TEKS IKLAN - Rizkha Eka Putri (Dialektologi, 2026)
https://docs.google.com/document/d/1dJmePg30YUXGOi2Lq9eRebcRjvuuDlun/edit?usp=sharing&ouid=102974828111434329464&rtpof=true&sd=true